Traditional Values and Educational Access: A Study of Girls' Schooling Rights in Pakpak Cultural Communities - Sudarwati, Lina; Hadriana; Napsiah, Napsiah; Erika; Tengku; Mohammad (IJORER : International Journal of Recent Educational Research, 2025)
Objective: this research examines the intricate processes contributing to educational development inequity among girls from impoverished female-headed households (pekka) in Pakpak communities at Pegagan Julu VIII Village, North Sumatra. The study explores the interplay between cultural traditions, socioeconomic constraints, and gender ideology that restricts girls' educational opportunities despite Indonesia's commitment to gender equality in educational development frameworks. Method: the investigation employed qualitative feminist methodology, gathering comprehensive life stories from seven Pakpak girls (ages 15-20) who experienced educational discontinuation. Data collection involved in-depth interviews, participatory observation, and focus group discussions with participants and their families, conducted over nine months of ethnographic fieldwork. Results: the analysis revealed that educational development inequity stems from two interlocking systems: patriarchal cultural structures and extreme poverty conditions. These systems create a "patriarchy-poverty nexus" that produces double marginalization of girls—first by systematically restricting their access to higher education in favor of male siblings, and second by imposing additional economic burdens wherein girls must abandon education to financially support their brothers' schooling. Significantly, mothers in these households often serve as unwitting agents reproducing patriarchal values despite their own marginalized position as household heads. Novelty: this study contributes uniquely to educational development discourse by identifying specific mechanisms through which traditional values intersect with economic hardship to create gender-based educational disparities in indigenous communities. Unlike previous research focusing solely on economic barriers, our findings illuminate how cultural interpretations of gender responsibility result in female educational sacrifice becoming normalized as familial duty, providing new insights for addressing educational inequity in traditional communities undergoing uneven development processes.